Penerapan Teknik Scavenger Hunt dalam Bimbingan Klasikal untuk Mengatasi Academic Burnout pada Siswa - Henny Mamahit; Hillary Reandsi (Kuras Institute, 2022)
Academic burnout is when students experience emotional exhaustion, cynicism, and reduced academic efficacy due to burnout and stress experienced for a long period. One of the factors that cause academic burnout is the monotonous learning method, so students are getting bored and not eager to take part in learning. Thus, an effort that can be made to overcome academic burnout is to provide classical guidance with interactive and fun methods such as involving the scavenger hunt game. This study aimed to apply the scavenger hunt game technique in classical guidance to overcome academic burnout. The subjects of this study were students of class 8th at SMP Kolese Kanisius, totaling 162 students. This study is a pre-experimental study with a one-group pretest-posttest design. This study's data collection techniques were MBI-SS, observation, interviews, and questionnaires. Based on the Wilcoxon test analysis results using SPSS, the Asymp. (2-tailed) value is 0.000. The Asymp value. (0.000) is smaller than the α value (0.05). These results indicate a significant difference between before and after being given classical guidance with the scavenger hunt game technique. So, it can be concluded that the scavenger hunt game technique through classical guidance can overcome academic burnout.